A chloroplast heat shock protein modulates growth and abiotic stress response in creeping bentgrass. (5th March 2021) - Sun, Xinbo; Huang, Ning; Li, Xin; Zhu, Junfei; Bian, Xiuju; Li, Huibin; Wang, Lihong; Hu, Qian; Luo, Hong
Abstract: Small heat shock proteins (sHSPs), a family of the ubiquitous stress proteins in plants acting as molecular chaperones to protect other proteins from stress‐induced damage, have been implicated in plant growth and development as well as plant response to environmental stress, especially heat stress. In this study, a chloroplast‐localized sHSP, AsHSP26.8, was overexpressed in creeping bentgrass ( Agrostis stolonifera L.) to study its role in regulating plant growth and stress response. Transgenic (TG) creeping bentgrass plants displayed arrested root development, slow growth rate, twisted leaf blades and are more susceptible to heat and salt but less sensitive to drought stress compared to wild‐type (WT) controls. RNA‐seq analysis revealed that AsHSP26.8 modulated the expression of genes in auxin signalling and stress‐related genes such as those encoding HSPs, heat shock factors and other transcription factors. Our results provide new evidence demonstrating that AsHSP26.8 negatively regulates plant growth and development and plays differential roles in plant response to a plethora of diverse abiotic stresses. Abstract : Small heat shock proteins (sHSPs) as molecular chaperons have been implicated in plant stress response and development. Characterization of AsHSP26.8, a sHSP, from Agrostis stolonifera L., revealed that it negatively regulates plant growth and development and plays differential roles in plant response to a plethora of diverse abiotic stresses.